Constructing Counter-narratives to Terrorism - A Comparative Analysis of Collective Resistance in the aftermath of the terror attacks in Bali and Norway - Balbi, Anne-Marie (Curtin University, 2019)
This dissertation explores the communicative dimensions of counter-terrorism (CT) and countering violent extremism (CVE), and how counter-narratives to terrorism and violent extremism (VE) emerge organically. Examining the symbolism of terror attack sites in Bali and Norway, it explores a) the discourses and local/national meanings attached to the sites b) the local resilience and collective action generated, conducting a discussion on the tangible insights and opportunities for emancipation for the field of CVE in general.